Reducing CO2 emissions in OECD countries: Do renewable and nuclear energy matter? - Saidi, Kais; Omri, Anis (Progress in nuclear energy (New series), 2020)
This study contributes to the existing environmental economics literature by examining the short- and long-run impacts of renewable and nuclear energy consumption on CO2 emissions in the case of 15OECD countries over the period 1990–2018 using both the Fully Modified OLS (FMOLS) and the vector error correction model approach (VECM) estimation methods. The results of the FMOLS show that: (i) investment in nuclear energy reduces CO2 emissions in Canada, Netherlands, Japan, Switzerland, Czech Republic and UK, (ii) investment in renewable energy reduces CO2 emissions in Belgium, Canada, France, Germany, Sweden, UK, US, Japan, Switzerland, Finland, Czech Republic; however, it increases CO2 emissions in Netherlands and South Korea, and (iii) both nuclear and renewable energy consumption reduces carbon emissions for the panel estimations. Moreover, the results of the VECM method show that nuclear and renewable energies reduce CO2 emissions in the long-term. Our results suggest that the best option to reduce CO2 emissions is to aim for a mix of nuclear and renewable energy. No need to choose. On the contrary: the two sources of energy are complementary. Policy implications are also discussed. [Display omitted] •Investment in nuclear energy and renewable energy reduced CO2 emissions in Belgium, Canada, France, Germany, Sweden, UK, US, Japan, Switzerland, Finland, Czech Republic; however, it increases CO2 emissions in Netherlands and South Korea.•Both nuclear and renewable energy consumption reduces carbon emissions for the panel estimations.•The best option to reduce CO2 emissions is to aim for a mix of nuclear and renewable energy.